(untitled) (Medico Legal Update, 2019)
The purpose of this study was to investigate the interaction between the activity ratio and the muscles of the lower extremity muscles according to the treadmill walking speed. The subjects measured the MVIC (Maximum Voluntary Isomeric Contraction) of the tibialis anterior, semitendinosus, medial gastrocnemius, biceps femoris using wireless surface electromyography. After walking for 1 minute at the speed of 3km/h, 4km/h, and 5km/h on the treadmill, muscle activities of the tibialis anterior, semitendinosus, medial gastrocnemius, biceps femoris. % MVIC (muscle activity/MVIC × 100) was used for the generalization of the measurements. In the treadmill walking at the speed of 3km/h, 4km/h, and 5km/h, the muscle activity ratios of the tibialis anterior, semitendinosus, medial gastrocnemius and the biceps femoris are as follows. There was a significant difference in muscle activity (P <0.05) in the tibialis anterior, medial gastrocnemius and the biceps femoris at 3km/h speed, 4km/h speed, 3km/h speed and 5km/h speed. There was a significant difference (P <0.05) in the semitendinosus muscle activity ratio between the 3 km/h and 4km/h speed walk, 3km/h speed and 5km/h speed walk, 4km/h speed walk and 5km/h speed walk. As the walking speed increased to 5km/h, the semitendinosus connected to the knee joint led to the gait rather than the ankle joint, so that it was found that the lower and the lower shoulder tend to walk with the tendency of bending and inner rotation